2016
DOI: 10.3329/bjog.v30i1.30505
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Asymptomatic Bacteriuria in Antenatal Women Coming to NRIMC&GH

Abstract: Objective(s):The aim of the study was to determine the prevalence of asymptomatic bacteriuria in pregnant women attending the antenatal OPD and to treat them. Also to identify the organisms causing asymptomatic bacteriuria and the risk factors in pregnant women.Materials and Methods: The present observational study was conducted in the Department of Obstetrics, NRI Medical College, Chinakakani, Mangalagiri from Aug-2012 to Aug-2014. Material for the study consisted of 100 urine samples obtained from asymptomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 10 publications
3
10
0
Order By: Relevance
“…Our study showed prevalence of asymptomatic bacteriuria was highest among 2 nd gravida (29.85%), followed by Primigravida (26.33%) and gravida 3 and above (23.07%). Similar association was seen in study by Ramalingam K et al 18 Like our study more cases of ASB in multigravidae (51.1%) than in primigravida was seen in the studies of Sujatha R et al and Roy et al 13,19 In this study, a higher rate of infection was detected in 3 rd trimester of pregnancy (53.65%), followed by second trimester (22.85%) and 1 st trimester (14.6%) which is similar to the results of the study by Rohini UV et al, Ramalingam K et al, and Saeed et al 9,18,20 But Yashodara et al reported incidence of ASB was highest in 1 st trimester, while studies done by Roy et al and Nath et al 21,19,22 reported higher incidence of ASB during 2nd trimester. Findings from all the studies concluded that screening for asymptomatic bacteriuria should be done in all the three trimesters of pregnancy which is necessary to prevent the dangerous complications associated with asymptomatic bacteriuria in pregnancy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study showed prevalence of asymptomatic bacteriuria was highest among 2 nd gravida (29.85%), followed by Primigravida (26.33%) and gravida 3 and above (23.07%). Similar association was seen in study by Ramalingam K et al 18 Like our study more cases of ASB in multigravidae (51.1%) than in primigravida was seen in the studies of Sujatha R et al and Roy et al 13,19 In this study, a higher rate of infection was detected in 3 rd trimester of pregnancy (53.65%), followed by second trimester (22.85%) and 1 st trimester (14.6%) which is similar to the results of the study by Rohini UV et al, Ramalingam K et al, and Saeed et al 9,18,20 But Yashodara et al reported incidence of ASB was highest in 1 st trimester, while studies done by Roy et al and Nath et al 21,19,22 reported higher incidence of ASB during 2nd trimester. Findings from all the studies concluded that screening for asymptomatic bacteriuria should be done in all the three trimesters of pregnancy which is necessary to prevent the dangerous complications associated with asymptomatic bacteriuria in pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies also conclude with the same recommendations. 18,21 Among the risk factors associated with ASB, highest prevalence was seen in patients with previous history of UTI (43.83%). Similar association is reported in studies of Rohini UV et al, Rajaratnam A et al 9,14 Lindsay E. Nicolle and many others.…”
Section: Discussionmentioning
confidence: 99%
“…In present study, prevalence of ASB is 9.2% which correlates with studies done by Sujatha R et al, [16] . 19,21,17 In present study Escherichia coli was the predominant isolate accounting 56.5%, similar results were reported by Sujatha [16][17][18]21,19,23 A study from Nigeria showed Staphylococcus aureus (72%) as commonest isolate and E. coli being the least (2%). 24 The organisms isolated can be faecal in origin colonizing in the periurethral area.…”
Section: Discussionsupporting
confidence: 88%
“…Enterococci including Gardnerella vaginalis and Ureaplasma ureolyticum are less common agents in UTIs. Ramalingam K et al [26] found that (50%) of bacteria isolates are Klebsiella spp. Muharram et al [27] and Ramalingam et al [26] also reported Klebsiella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Ramalingam K et al [26] found that (50%) of bacteria isolates are Klebsiella spp. Muharram et al [27] and Ramalingam et al [26] also reported Klebsiella spp. as the most common micro-organism.…”
Section: Discussionmentioning
confidence: 99%